Producing offspring in Armadillidium vulgare: Effects of genetic diversity and inbreeding. Issue 2 (1st March 2018) - Durand, Sylvine; Loiseau, Vincent; Prigot, Cybèle; Braquart‐Varnier, Christine; Beltran‐Bech, Sophie
Abstract : Genetic diversity is known to be correlated to fitness traits, and inbred individuals often display lower values for life history traits. In this study, we attempt to quantify how inbreeding affects such traits in the terrestrial isopod Armadillidium vulgare by performing inbred and non‐inbred crosses under laboratory conditions. We estimated genetic characteristics of parents and offspring, and related them to fecundity and fertility measures, as well as offspring growth and survival. Our study shows that a decrease in offspring number might result from mortality around birth, but not to changes in fecundity, fertilization rate, or developmental failure between inbred and non‐inbred crosses. More heterozygous females tended to be bigger and had a higher fecundity, which could have implications in mate choice. No effect of inbreeding was detected on offspring growth and survival. These results can be related to previously observed effects of genetic characteristics on mating strategies in A. vulgare, and could shed light on mechanisms of inbreeding avoidance in this species.